Comparative Study of the Effectiveness of Knee Formula 1 and Knee Formula 2 for Knee Pain And Range of Motion of Knee Joint in Patients with Osteoarthitis Bang Yai Hospital, Bang Yai, Nonthaburi - อุดมพิทยาสรรพ์ เจษฎา; สยอวรรณ วินัย; คตวงค์ วรายุส; แก้ววิเศษ ณัฐสุดา; ศิรมณีรัตน์ อิศรา (Princess of Naradhiwas University Journal, 2019)
This quasi-experimental study aimed to compare knee pain level of patients with knee osteoarthritis between using herbal knee pack formula 1 and 2, in order to relieve osteoarthritis. Sample was 40 patients who received knee pain treatment at a Thai traditional medicine clinic in Bangyai Hospital, Nonthaburi Province. Participants were aged between 40-85, and were suffering knee pain for more than 6 months. The instruments were: 1) Westerm Ontario MacMaster Universities Osteoarthritis Index (WOMUOI), and 2) Knee Movement Measurement, using goniometers. The researchers collected data at the Thai traditional medicine clinic of Bang Yai Hospital. Statistics used for data analysis were frequency, percentage, mean, standard deviation, and independent t-test. Results of this study revealed that the differences between using the herbal knee pack formula 1 and 2 in terms of knee pain, and knee joint’s range of motion were not statistically significant (p>.05). However, this study suggested that herbal knee pack formula 1 and 2 could relieve knee osteoarthritis in patients. It can help to reduce knee pain, and increase knee’s range of motion. But treatment must be maintained at least 4 times continuously